Cover Picture: PI by NMR: Probing CH–π Interactions in Protein–Ligand Complexes by NMR Spectroscopy (Angew. Chem. Int. Ed. 35/2020). Issue 35 (20th July 2020) - Platzer, Gerald; Mayer, Moriz; Beier, Andreas; Brüschweiler, Sven; Fuchs, Julian E.; Engelhardt, Harald; Geist, Leonhard; Bader, Gerd; Schörghuber, Julia; Lichtenecker, Roman; Wolkerstorfer, Bernhard; Kessler, Dirk; et al.
Abstract : The CH– π interactions between the CH donor groups of Trp81‐ζ and Trp81‐η with the aromatic π‐systems of ligand 3 (stylized in blue and green, respectively) are illustrated in the cover picture. The backdrop shows an NMR chemical shift scale into which the Trp81 CH cross peaks are schematically drawn. In the complexed form, the CH groups are shifted by up to 2.3 ppm as they are shielded by the aromatic ring systems of the ligand. As explained by G. Platzer, M. Mayer et al. in their Research Article on page 14861, these upfield shifts are indicative of favorable CH–π interactions, which are difficult to detect directly in solution by other methods.